Does a narrative retelling task improve the assessment of language proficiency in school-aged children born very preterm?. (1st December 2020) - Stipdonk, Lottie W.; Dudink, Jeroen; Reiss, Irwin K.; Franken, Marie-Christine J. P.
ABSTRACT: Almost half of the children born very preterm (VP) experience language difficulties at school-age, specifically with more complex language tasks. Narrative retelling is such a task. Therefore, we explored the value of narrative retelling assessment in school-aged children born VP, compared to item-based language assessment. In 63 children born VP and 30 age-matched full-term (FT) controls Renfrew's Bus Story Test and Clinical Evaluation of Language Fundamentals were assessed. The retelling of the Bus Story was transcribed and language complexity and content measures were analyzed with Computerised Language Analysis software. Narrative outcomes of the VP group were worse than that of the FT group. Group differences were significant for the language complexity measures, but not for the language content measures. However, the mean narrative composite score of the VP group was significantly better than their mean item-based language score, while in the FT group the narrative score was worse than the item-based score. Significant positive correlations between narrative and item-based language scores were found only in the VP group. In conclusion, in VP children narrative retelling appears to be less sensitive to detecting academic language problems than item-based language assessment. This might be related to the mediating role of attention in item-based tasks, that appears not to affect more spontaneous language tasks such as retelling. Therefore, in school-aged children born VP we recommend using narrative assessment, in addition to item-based assessments, because it is more related to spontaneous language and less sensitive to attention problems.